Development of sensitivity to orthographic errors in children: An event-related potential study. (1st September 2017) - Heldmann, Marcus; Puppe, Svetlana; Effenberg, Alfred O.; Münte, Thomas F.
Highlights: Sensitivity to orthographic errors develops over grade school years. Orthographic errors give rise to specific electrophysiological components. Electrophysiological markers of errors are age-dependent. Abstract: To study the development of orthographic sensitivity during elementary school, we recorded event-related brain potentials (ERPs) from 2nd and 4th grade children who were exposed to line drawing of object or animals upon which the correctly or incorrectly spelled name was superimposed. Stimulus-locked ERPs showed a modulation of a frontocentral negativity between 200 and 500 ms which was larger for the 4th grade children but did not show an effect of correctness of spelling. This effect was followed by a pronounced positive shift which was only seen in the 4th grade children and which showed a modulation of spelling correctness. This effect can be seen as an electrophysiological correlate of orthographic sensitivity and replicates earlier findings in adults. Moreover, response-locked ERPs triggered to the children's button presses indicating orthographic (in)-correctness showed a succession of waves including the frontocentral error-related negativity and a subsequent negativity with a more posterior distribution. This latter negativity was generally larger for the 4th grade children. Only for the 4th grade children, this negativity was smaller for the false alarm trials suggesting a conscious registration of the error in these children.